2016
DOI: 10.1186/s12944-016-0279-3
|View full text |Cite
|
Sign up to set email alerts
|

AGTR1 rs3772622 gene polymorphism increase the risk of nonalcoholic fatty liver disease patients suffer coronary artery disease in Northern Chinese Han population

Abstract: BackgroundCardiovascular disease (CAD) responsible and nonalcoholic fatty liver disease (NAFLD) are both metabolic diseases, and they are mostly influenced by genetic factors. The aim of our study is to evaluate the relationship between angiotensin II type-1 receptor (AGTR1) gene rs3772622 polymorphisms and the risk of developing coronary artery disease (CAD) in Chinese patients with NAFLD.MethodsGenotype for AGTR1 rs3772622 in 574 NAFLD patients with CAD or 589 NAFLD patients without CAD, 332 CAD patients exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The hypothesis that alcoholic and non-alcoholic fatty liver disease may differ in some aspects regarding genetic predisposition despite all similarities, is supported by the results from a Japanese cohort, which found differences between the two disease groups when analysing 10 different polymorphisms [33]. The second potential conclusion is that ethnic and environmental differences lead to diverging genetic risk factors for fatty liver disease in different regions of the world, as our study comprised only Caucasian patients, while studies reporting AGTR1 polymorphisms as a risk factor for NAFLD included mainly Asian patients [5,6,20]. It is known that ethnic background affects survival in HCC patients, which may not only be linked to genetic predisposition but also to the etiology of HCC, which differs across regions worldwide, and to access to surveillance and treatment programs [34][35][36].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The hypothesis that alcoholic and non-alcoholic fatty liver disease may differ in some aspects regarding genetic predisposition despite all similarities, is supported by the results from a Japanese cohort, which found differences between the two disease groups when analysing 10 different polymorphisms [33]. The second potential conclusion is that ethnic and environmental differences lead to diverging genetic risk factors for fatty liver disease in different regions of the world, as our study comprised only Caucasian patients, while studies reporting AGTR1 polymorphisms as a risk factor for NAFLD included mainly Asian patients [5,6,20]. It is known that ethnic background affects survival in HCC patients, which may not only be linked to genetic predisposition but also to the etiology of HCC, which differs across regions worldwide, and to access to surveillance and treatment programs [34][35][36].…”
Section: Discussionsupporting
confidence: 61%
“…Nearly 600 patients with NAFLD with and without coronary artery disease, more than 300 patients without NAFLD but with coronary artery disease, and more than 300 healthy control patients were genotyped for the AGTR1 rs3772622 polymorphism. While the authors did not detect a significant difference in the distribution of the AGTR1 rs3772622 genotypes between patients with and without NAFLD, they noted a statistically significant association with coronary artery disease, suggesting that the AGTR1 rs3772622 polymorphism might be associated with severe metabolic sequelae compared to NAFLD alone [20]. In a third study [6], several AGTR1 polymorphisms, including rs3772622, were tested for their association with NAFLD in different ethnic subgroups.…”
Section: Discussionmentioning
confidence: 97%
“…AGTR1 is the type 1 receptor of angiotensin II. Studies have demonstrated AGTR1 variant and polymorphisms were correlated with the risk of NAFLD ( 36 , 37 ). Lower hepatic AGTR1 expression was found in SS patients in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown a mechanistic role of RAS and AngII on hepatic fibrosis (Yoshiji et al, 2001; Yokohama et al, 2004), while those reporting the effect of ARB on NAFLD in murine models did not elucidate the underlying mechanisms (Sugimoto et al, 2006; Sturzeneker et al, 2011; Kato et al, 2012). AngII is a pro-inflammatory and pro-oxidant factor, and its receptor AT1-R is present on both normal and diseased liver parenchyma cells and associated with NAFLD (Yoneda et al, 2009; Liu et al, 2016). Irbesartan is a typical ARB, and has shown considerable therapeutic effects in both animal models and in hypertensive patients with NAFLD.…”
Section: Introductionmentioning
confidence: 99%